Manfaat Membaca Cerita Dongeng Kancil yang Berjudul : Kisah Kancil dan Buaya untuk Anak dalam Membentuk Karakter - Revika Angeli Febrina; Herlinda Herlinda (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
The story of Kancil and Crocodile is a fairy tale that is often read by children. This study analyzes the moral impact of the fairy tale "Kancil and Crocodile" on the development of children's character, especially those aged six years. The story of the clever Kancil and the strong Crocodile, where Kancil uses his cunning to deceive Crocodile in order to achieve his goals. This study aims to analyze the impact of this story on the formation of children's character, especially related to the moral and ethical values ​​contained in the story. Through a qualitative approach, the researcher found that although Kancil showed cleverness in dealing with problems, his deceptive actions could provide an example of negative behavior for children. This has the potential to affect their way of thinking about honesty and social ethics. The results of the study indicate that this story has good and bad potential, so that they can distinguish between right and wrong actions. In addition, this story teaches values ​​such as cooperation and empathy through the experience of Crocodile who feels cheated. Thus, although there are negative aspects of Kancil's cunning, there are also positive lessons that can be taken for children's character development.